Możliwość odstąpienia od uzasadnienia decyzji (jego ograniczenia) na mocy Kodeksu postępowania administracyjnego i przepisów szczególnych: [Possibility when decision-makers have permission to failure to give (or to limit) the justification for the administrative decision under the Code of Administrative Procedure and provisions of other legal acts] (Studia Prawnicze / The Legal Studies, 2018)
Celem niniejszego artykułu jest przedstawienie instytucji odstąpienia od uzasadnienia decyzji administracyjnej na gruncie Kodeksu postępowania administracyjnego i przepisów pozakodeksowych. Głównym problemem badawczym jest wskazanie, do jakiego typu decyzji instytucja ta będzie miała powszechne zastosowanie, a w jakich przypadkach organy będą zasadniczo sporządzały pełną treść uzasadnienia. Dokonano zatem analizy przepisów Kodeksu postępowania administracyjnego i przepisów pozakodeksowych, orzecznictwa sądów i poglądów doktryny dotyczących powyższej instytucji. The article aims to present the legal institution of failure to give justification for administrative decision (when decision-makers may choose not to give reasons for administrative decision), in accordance with the Code of Administrative Proceedings (CAP) and provisions of other legal acts. The main research question is to indicate in which type of decision this legal institution will be widely used, and in which cases the decision-makers will prepare a “full” content of the justification. The provisions of the CAP and other non-code provisions, court decisions and doctrinal opinions regarding the above institution were analyzed.